COMPARATIVE QUALITATIVE AND QUANTITATIVE ANALYSIS OF THE TERSKO SULAKSKAY LOWLAND'S AREAS - M. E. Kotenko; E. M. Gadjieva (Вестник Дагестанского государственного технического университета: Технические науки)
Data are obtained in the comparative analysis of cartographic materials on the Tersko-Sulaksky lowland (50-2000 years). In comparison with fifties the increase in extent of salinization of soils and their area more than twice is revealed, reduction of the area of meadow-chestnut soils honor by 3 times that is connected with an aridization and with increase in anthropogenous influences.